No Clinically Significant Difference Between Adult and Pediatric IKDC Subjective Knee Evaluation Scores in Adults. (September 2017) - Stegmeier, Nicole; Oak, Sameer R.; O'Rourke, Colin; Strnad, Greg; Spindler, Kurt P.; Jones, Morgan; Farrow, Lutul D.; Andrish, Jack; Saluan, Paul
Background: Two versions of the International Knee Documentation Committee (IKDC) Subjective Knee Evaluation form currently exist: the original version (1999) and a recently modified pediatric-specific version (2011). Comparison of the pediatric IKDC with the adult version in the adult population may reveal that either version could be used longitudinally. Hypothesis: We hypothesize that the scores for the adult IKDC and pediatric IKDC will not be clinically different among adult patients aged 18 to 50 years. Study Design: Randomized crossover study design. Level of Evidence: Level 2. Methods: The study consisted of 100 participants, aged 18 to 50 years, who presented to orthopaedic outpatient clinics with knee problems. All participants completed both adult and pediatric versions of the IKDC in random order with a 10-minute break in between. We used a paired t test to test for a difference between the scores and a Welch's 2-sample t test to test for equivalence. A least-squares regression model was used to model adult scores as a function of pediatric scores, and vice versa. Results: A paired t test revealed a statistically significant 1.6-point difference between the mean adult and pediatric scores. However, the 95% confidence interval (0.54-2.66) for this difference did not exceed our a priori threshold of 5 points, indicating that this difference was not clinically important. Equivalence testing with an equivalence region of 5 points further supported this finding. The adult and pediatric scores had a linear relationship and were highly correlated with an R 2 of 92.6%. Conclusion: There is no clinically relevant difference between the scores of the adult and pediatric IKDC forms in adults, aged 18 to 50 years, with knee conditions. Clinical Relevance: Either form, adult or pediatric, of the IKDC can be used in this population for longitudinal studies. If the pediatric version is administered in adolescence, it can be used for follow-up into adulthood.